Water saving technology package to improve shallot productivity for smallholder farmers in eastern Indonesia - Ahmad Suriadi; Lia Hadiawati; Moh Nazam (Jurnal Agro, 2020)
Dryland usage for shallot cultivation is very potential in West Nusa Tenggara (NTB) Province Indonesia. However, its utilization is faced with various obstacles such as soil low fertility, limited water availability, and high pest and disease attacks. Currently, farmers apply flood and furrow irrigation methods for shallot cultivation in NTB Province, which may not suitable on dryland, especially on coarse texture soils. The purpose of this study was to obtain a package of water-saving technology to increase the productivity of shallots in the dryland of NTB. There were three treatments of technology packages tested laid as Randomized Block Design: A (Trichoderma sp., bio-urine liquid fertilizer, sprinkler irrigation; B (bio-urine liquid fertilizer, furrow irrigation); and C (farmer practice), involving farmer group members from planning to evaluating for the technology package that being tested. The amount of water used was measured using a water meter. The results showed that package A had achieved the highest shallot yield at 31.6 tons ha-1, which was 14% and 45% higher compared to package B and C, respectively. Package A was also able to save water irrigation for 62.1% and 95.8% compared to package B and C, respectively. Thus, sprinkler irrigation not only can increase shallot yield but also better in saving water irrigation. Penggunaan lahan kering untuk budidaya bawang merah di Nusa Tenggara Barat sangat potensial. Namun hal tersebut terkendala oleh beberapa masalah seperti rendahnya kesuburan tanah, terbatasnya air irigasi, dan tingginya gangguan hama dan penyakit. Saat ini, petani di NTB mengairi tanaman bawang merah dengan cara direndam atau leb yang belum tentu sesuai dengan kondisi lahan kering terutama pada tanah dengan tekstur berpasir. Tujuan dari penelitian ini adalah untuk mendapatkan paket teknologi hemat air yang dapat meningkatkan hasil dan pendapatan budidaya bawang merah di lahan kering. Ada tiga perlakuan paket teknologi yang ditata dengan rancangan acak kelompok yaitu A (Trichoderma sp., pupuk organik cair bio-urine, dan irigasi curah); B (pupuk organik cair bio-urine, dan pengairan leb), dan paket C (cara petani: pengairan leb). Penelitian ini melibatkan petani mulai dari perencanaan sampai evaluasi paket teknologi yang diujikan. Hasil penelitian menunjukkan bahwa paket A menghasilkan produksi tertinggi sebesar 31,6 t ha-1, atau 14% dan 45% ebih tinggi dari paket B dan C. Paket A juga mampu menghemat air irigasi sebanyak 62,1% dan 95,8% dibandingkan dengan paket B dan C. Dengan demikian, penggunaan irigasi curah mampu meningkatkan hasil dan menghemat air irigasi.